A sourcebook for ancient Greek : grammar, poetry, and prose - Tomarchio, John (The Catholic Education Press, 2022)
"This book was designed for students transitioning from the study of Greek grammar to translation of texts. It was developed in classroom use for classroom use, in the context of an integrated Great Books program in liberal arts and sciences. It is meant for students not only of Classics, but more, for students of Humanities interested in direct engagement of primary sources. Each Greek text offered for translation was chosen for its theoretical interest as well as the interest of its Greek. The selections of Greek literature offered in this Sourcebook are wide-ranging. The indisputable standard of excellence for classicists is of course the Attic dialect of Athens in its glory. However, this Sourcebook is meant for students of liberal arts and sciences whose interests range far more widely. Thus, it does not hesitate to extend not only backward to the archaic Greek of Homer, but also forward to the koine Greek of the Alexandrian and Roman empires. Greek works were chosen for being seminal to Western thinking today, chosen to give students of Western arts and sciences introductions to its Greek sources. Naturally, Greek grammar is taught to the newcomer analytically and sequentially, but the continuing student needs to synthesize these distended enumerations of elements and principles. Accordingly, grammatical synopses are not appended as reference tables but placed front and center as objects of study. The grammar tables offer synoptic views of integral parts of Greek grammar to show the form and logic of the whole part of speech or part of a sentence. On the basis of these tables, detailed grammatical notes and commentary appended to Greek selections that follow are tailored for continuing students." --Publisher description.